The stream fish fauna from the rio Machado basin, Rondônia State, Brazil - Casatti, Lilian [UNESP]; Pérez-Mayorga, María Angélica [UNESP]; Rogério Carvalho, Fernando [UNESP]; Lourenço Brejão, Gabriel [UNESP]; da Costa, Igor David (Pensoft Publishers, 2013)
The rio Machado (also known as Ji-Paraná) is a tributary of the rio Madeira in the Amazon basin. Currently, the rio Madeira contains the greatest fish species richness of the world, with approximately 1,000 species. The present study presents the fish inventory from streams of the rio Machado basin. In total, 75 stream reaches, 80 meter-length, randomly selected, were sampled in 2011 (August to October) and 2012 (June to July). Overall, 22,875 fish in eight orders, 32 families, 89 genera, and 140 species were collected. Richness estimators indicate that almost 90% of the expected richness was registered. The great majority of specimens (52.2%) was represented by small sized piabas such as Serrapinnus aff. notomelas, Moenkhausia collettii, Serrapinnus microdon, and Hemigrammus melanochrous. Of the total richness, 25 species were restricted to 9°00′ S and 10°00′ S; among them, 14 were exclusive to the lower portion of the basin, which exhibits the larger proportion of native vegetation covering. © 2013 Check List and Authors.